2015
DOI: 10.4172/2155-6148.1000554
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Pulmonary Complications and Associated Factors among Surgical Patients

Abstract: Introduction: Postoperative complications, although other complications may occur, involving the respiratory tract is the most frequent one that contribute to the greatest peri operative morbidity and mortality. The occurrence of postoperative pulmonary complications varies depending on the clinical treatment setting, the kind of surgery and the definition used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
2
1
0
Order By: Relevance
“…In our study, patients with intra-operative blood loss of >500 ml were more likely to develop PPC than patients with blood loss of less than 500 ml which was in line with previous studies ( 12 , 30 ). Excessive blood loss during surgical procedures calls for judicious replacement to restore a normovolemic state.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, patients with intra-operative blood loss of >500 ml were more likely to develop PPC than patients with blood loss of less than 500 ml which was in line with previous studies ( 12 , 30 ). Excessive blood loss during surgical procedures calls for judicious replacement to restore a normovolemic state.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, different types of pulmonary complications were identified in the post-operative period. Among those complications, pneumonia was the most common, followed by respiratory infection and respiratory failure, which is similar to other previous studies (24,(28)(29)(30).…”
Section: Discussionsupporting
confidence: 91%
“…A Tanzanian study found that PHRF accounted for 8.3% of morbidity and mortality [6]. In Ethiopia, a retrospective study conducted in Addis Ababa and Gondar revealed that pulmonary complications were the most common postoperative complications [7]. And in Uganda, a multicenter study conducted on 485 patients, showed 23.9% of the patients were hypoxemic within the rst 15 minutes of arriving at the post-anesthesia care unit and needed oxygen supplementation.…”
Section: Introductionmentioning
confidence: 99%
“…3 La disfunción pulmonar postquirúrgica (DPP) es una complicación bastante común después de una cirugía, en especial en cirugía cardiaca; 40% de los admitidos a la UCI secundario a DPP presentan insuficiencia respiratoria, y hasta el momento aún se desconoce el manejo que pueda reducir su incidencia (Tabla 1). 4,5 Las manifestaciones clínicas de la DPP incluyen derrame pleural (27-95%), atelectasia (16.6-88%), hipoxe-RESUMEn Introducción: Las complicaciones postoperatorias a nivel pulmonar son causa de morbilidad y mortalidad, particularmente cuando desarrollan síndrome de dificultad respiratoria aguda y requieren ventilación mecánica; uno de los métodos empleados para pacientes que no responden al manejo ventilatorio convencional es la posición prono; sin embargo, hay poca evidencia sobre ventilación en prono en pacientes quirúrgicos abdominales. Material y métodos: Se revisó una cohorte de pacientes ventilados en prono para analizar el comportamiento de los cortocircuitos pulmonares y el índice Pao 2 /Fio 2 antes, durante y después de la ventilación en prono.…”
Section: Introductionunclassified
“…6,7 El manejo con ventilación en posición prono está recomendado para aquéllos con relación Pao 2 /Fio 2 < o igual a 150; sobre esto se conocen en la literatura contraindicaciones absolutas y relativas, enlistándose el estado postquirúrgico de abdomen y específicamente abdomen abierto como una contraindicación relativa, sin existir un sustento objetivo y de peso para ello. [5][6][7] El objetivo de este manuscrito es describir una cohorte de pacientes postquirúrgicos con abdomen abierto que requirieron manejo ventilatorio en posición prono.…”
Section: Introductionunclassified